2007
DOI: 10.1080/07399330701615341
|View full text |Cite
|
Sign up to set email alerts
|

Health-Promoting Aspects of a Paid Job: Findings in a Qualitative Interview Study With Elderly Women in Sweden

Abstract: This article is one aspect of a larger, qualitative interview study and deals with health-promoting aspects of gainful employment, as experienced by a group of elderly Swedish women. Through these interviews we demonstrate the central importance of outside employment for many of the women, although they belonged to a generation where outside work conflicted with societal norms. We will illustrate a wide variety of ways in which gainful employment can contribute to women's well-being and, ultimately, their heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…A sense of humour was pointed out as being part of these women's personality, and they sought ways to use it. They often joked and created settings for jokes in women-dominated situations, such as their workplaces [10]. This finding goes against the general assumption, saying that men create humour while women just enjoy it [12], and agrees with other findings in health research on women [29].…”
Section: On Findingssupporting
confidence: 73%
“…A sense of humour was pointed out as being part of these women's personality, and they sought ways to use it. They often joked and created settings for jokes in women-dominated situations, such as their workplaces [10]. This finding goes against the general assumption, saying that men create humour while women just enjoy it [12], and agrees with other findings in health research on women [29].…”
Section: On Findingssupporting
confidence: 73%
“…Combining roles has been reported to drain one's energy due to difficulties meeting the given role demands and may result in a lower level of life satisfaction and poorer physical health (Elgar & Chester, 2007). Successfully balancing multiple roles also has been found to increase women's well-being (Campione, 2008;Forssén & Carlstedt, 2007), provide important psychological input, heighten selfesteem, and enhance social relationships (Barnett, 1999). Research on pregnancy in relation to work is rare, however, and such studies are mainly British.…”
mentioning
confidence: 96%
“…Unemployment, when these latent functions are lacking, can thus result in ill-health. Some of these latent functions connected to paid work were expressed in a qualitative study of elderly women in Sweden [ 11 ]. The study showed the positive impact of work for health, as paid work gave a meaning to the women, a room of their own as well as self-esteem and social support.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified only a few qualitative studies about social determinants of health, based on gender theories. One [of them, based on feminist theory, analysed interviews among 20 elderly Swedish women and found that paid work was experienced as health-promoting through giving meaning, self-esteem, social relations, a room of one’s own, a basis for self-determination and independence (from men), freedom from constant availability for the needs of their families, and it strengthened them in unequal, or even abusive, partner relationships [ 11 ]. Another theoretically driven paper showed that stereotypical gender practices in housework can increase experiences of stress among women and men.…”
Section: Introductionmentioning
confidence: 99%